Mathematical Literacy Skills of Junior High School Students in Border Schools in Solving Minimum Competency Assessment-Based Problems - Leton, Samuel Igo; Lakapu, Meryani; Dosinaeng, Wilfridus Beda Nuba; Fitriani, Nelly; Amsikan, Oktovianus Yongki (Jurnal Pendidikan MIPA, 2024)
Literacy skills are one of the mathematical abilities that all students need to have in today's global era. However, not all students in border schools have good mathematical literacy skills. This type of research is descriptive qualitative which aims to get an overview of the mathematical literacy skills of students in border areas in solving Minimum Competency Assessment-based problems and also identify factors that influence these skills. This study involved all 57 seventh grade students in the first semester of SPMN Lorontuan Atambua - NTT. The test questions were four numbers in the form of true and false, multiple correct answers and short form. The results of the analysis found that some of them could not read fluently; not all students had a good understanding of basic mathematical concepts; lack of learning experience of contextual problems or story problems that caused them to have difficulty understanding the problem, choosing the mathematical concept used to answer the problem and could not analyze the information provided. The reconstruction that we provide is the need to build a strong mathematical understanding by designing mathematics learning that integrates local wisdom and technology and provides them with varied learning experiences on story problems.         Keywords: math skills, literacy, schools at the border. DOI: http://dx.doi.org/10.23960/jpmipa/v25i2.pp728-751